Análisis de la interferencia lingüística y su influencia en la comunicación efectiva en estudiantes de básica superior de la Unidad Educativa Eloy Alfaro Delgado. - Atupaña Yautibug, Luis Eduardo (2024)
The global problem of language interference and its impact on effective communication presents itself as a significant barrier in multicultural and multilingual contexts. Addressing this problem requires educational strategies and awareness programs that foster intercultural understanding and the ability to recognize and mitigate language interference. Therefore, “THE AIM OF THIS STUDY IS TO ANALYSE LANGUAGE BARRIERS AND ITS INFLUENCE ON EFFECTIVE ENGLISH COMMUNICATION AT ELOY ALFARO DELGADO EDUCATIONAL UNIT” This can be a quantitative, descriptive, field study and non-experimental design methodology. For this, a sample of 46 students was used, to whom a 10-question survey with a 5-point Likert scale was applied. As a result, although interference is present in a general proportion close to 20%, it is a constant element in communicative assessment, the existence of interferences between the native and target language, which makes communication more difficult. That is why a proposal has been put forward to support language proficiency to reduce them. In implementation this, there will be a reference that allows its use in the Kichwa-Spanish linguistic context, in order to decrease the gaps between both languages, and how to teach English to speakers.